SC33 Simulation in supported return to training Paediatrics. (3rd November 2019) - Sampath, Sunitha
Abstract : Background: Trainees take break in their training due to various reasons. Trainees who have been out of training programme feel anxious, under confident and deskilled which can lead to their underperformance thus putting patient's safety at risk. They have reported lack of support to their return to work (AOMRC 2016). Studies have shown that supported return to work (RTW) programme helps them to transition back to their clinical activities smoothly. Simulation helps to build their competence and confidence (Kiernan 2018). Summary of work: Our school of paediatrics has very high proportion of RTW trainees due to large female proportion of trainees, family friendly environment and our efforts to support other out of programme experiences. There are around 50 (12.5%) trainees/year who are out of programme in our school and around 10–15 trainees/year as direct entrants to ST4 emphasising the need for robust programme. We estimated need for around 8 RTW training days for our trainees to meet our aims, we planned out study days, evaluation strategy and secured funding from HEE through a carefully planned business plan. Study day used simulation training with scenarios that were mapped to RCPCH curriculum covering important areas of acute management, neonatal and safeguarding scenarios while focussing on leadership, team working, communication and human factors. All participants got the opportunity to take part in simulation and debriefing. Their simulated role and the case management reflected the work and position they were returning into. Day also touched upon mentoring, peer support, resilience, mindfulness, clinical guidelines updates, changes to assessments/e-portfolios, signposting, advice and guidance. Course was also offered to the nurses acknowledging that their involvement enhances simulation training for all. The effectiveness of the training day was evaluated by the feedback forms. Results: Our first ever RTW training day received excellent feedback with 86% grading it as excellent while rest as very good. Trainees expressed improved confidence and preparedness and requested for more simulation. 100% felt it's valuable and recommended the day to be split into two days where one day would concentrate on simulation including skill stations. Conclusion: Our effort to establish a good RTW training has shown that trainees really appreciate it and would like more of it gain confidence for an effective patient care. Going forwards, we envisage more simulation training, onsite child care facilities and developing VLE package. The principles of this course can be applied to all other schools with individual adaptation. References: AOMRC 2016: Return to Practice Guidance 2017 Revision:https://www.aomrc.org.uk/reports-guidance/revalidation-reports-and-guidance/return-practice-guidance-2017-revision/ Kiernan L (2018). Evaluating competence and confidence using simulation technology. Nursing :48(10): 45–52.